Pengaruh Good Corporate Governance Terhadap Financial Distress Dengan Profitabilitas Sebagai Variabel Moderating - Hanifa, Sarah; Saleh, Mustaruddin; Afifah, Nur (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2024)
This study analyzes the effect of governance attributes which include the board of commissioners, audit committee, institutional ownership and managerial ownership on financial distress with profitability as the moderating variable. The analysis used agency theory to explain the findings. This study used multiple linear regression analysis and Moderated Regression Analysis (MRA) with testing using Eviews 12. The methodology used was quantitative approach and the data used was secondary data. This study used panel data with details of 471 data from 157 manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. All governance attributes have positive influence on financial distress except for managerial ownership. Profitability (ROA) has succeeded in strengthening the relation between the board of commissioners, institutional ownership and managerial ownership of financial distress. Meanwhile, profitability weakens the relation between the audit committee and financial distress.